Determination of Total Boron in Soil by Alkaline Fusion-Inductively Coupled Plasma Mass Spectrometry - Jia-shu CHEN; Xiong XIONG; Jin-mei DUAN; Ying-lin CHEN; Jia-jun JIANG; Hong-hui ZHU (Zhipu Xuebao)
The traditional methods of boron determination mainly include spectrophotometry, titration and electrochemical method, etc. These methods are complicated, time-consuming and easy to be affected by external environmental factors. With the development of analytical technology, inductively coupled plasma mass spectrometry (ICP-MS) has gradually become the preferred method for the determination of trace and ultra-trace elements in environmental samples due to its advantages of simple operation, high sensitivity and high selectivity. For ICP-MS analysis, it is very important to choose a appropriate pretreatment method. The commonly used acid hydrolysis method is not only time-consuming, but also has high operational safety risk and environmental pollution, and boron is easy to volatilize in hydrofluoric acid environment, which leads to loss of the analyte. Alkali melting method is very effective for the decomposition and dissolution of insoluble substances. By melting the soil sample with alkaline flux, the boron element in the sample was completely released, and the melt was dissolved with acid, and then analyzed by ICP-MS. This method can effectively avoid the volatilization loss of boron element in the traditional acid solution method, and improve the accuracy and reliability of the determination. In this study, a method of alkali melting and ICP-MS was established for the determination of total boron in soil. The accuracy and reliability of the method were ensured by optimizing the experimental conditions, such as melting temperature, melting time and acid dissolution conditions. The results showed that after adding 2.0 g Na2CO3, soil samples were heated at 950 ℃ for 20 min, and then hydrochloric acid solution (1:1, V/V) was used to dissolve the frit, affording the best dissolution effect. With the proposed pretreatment, the linear relationship of total boron concentration in the range of 0-100 μg/L is good, and the linear correlation coefficient is 0.999 5. The limit of detection and the limit of quantification are 0.20, 0.65 mg/kg, respectively. The precision (RSD, n=6) is 1.92%-3.79%, with the relative error (RE) ranging from −0.32% to 3.69%, and the relative standard deviation (RSD, n=6) of the actual sample is 0.99%-1.82%. Compared with inductively coupled plasma-optical emission spectrometer (ICP-OES), the data stability of this method is better, the working efficiency is higher.